“Polarización Política en Elecciones Seccionales, caso de estudio Parroquia Bolaspamba, Cantón Zapotillo, Provincia de Loja, año 2023” - Córdova Rogel, Génesis Jariley (2025)
The objective of this curricular integration work is to determine the existence of political polarization in the Bolaspamba parish, Zapotillo canton, Loja province, year 2023. To achieve this purpose, two specific objectives were proposed: first, to describe the results of the 2023 sectional elections in Bolaspamba parish; and second, to identify the variables that show the political polarization in Bolaspamba parish. For this purpose, the electoral results were obtained from the CNE's digital platform and the work plans of each candidate. Nine qualitative and three quantitative variables that show polarization were identified according to theoretical concepts on the subject, which led to the creation of data collection instruments that were then applied. The interviews were applied to the candidates for the presidency of the GAD Parroquial de Bolaspamba in 2023, and the surveys were applied to 256 local voters (both instruments kept questions related to the qualitative variables). As a result, 6 of the 9 qualitative variables were identified in the parish, and as an additional point, the polarization index was measured with the 3 quantitative variables. In the 2023 sectional elections, 3 out of 5 political movements candidates were from the extreme right, and most of the electorate was inclined in that direction. The qualitative variables identified allowed us to know the negative effects that the political phenomenon has had in the parish, and when measuring the index of political polarization with the quantitative variables, it turned out to be 65.36%.